ASSISTANCE IN THE DEVELOPMENT OF BUSINESS DIVERSIFICATION TO OPTIMIZE INCOME FOR WOMEN'S COOPERATIVES IN BLITAR DISTRICT - Murdiono, Achmad; Zen, Fadia; Istanti, Lulu Nurul (JOURNAL OF SUSTAINABLE COMMUNITY SERVICE, 2023)
The presence of Women's Cooperatives in Indonesia holds significant importance, despite the limited number of large-scale Women's Cooperatives. These cooperatives play a crucial role in supporting the government's efforts to address national challenges such as unemployment reduction, enhanced health outcomes, improved education, and the resolution of gender-related issues. Analysis of the objectives of this initiative reveals two primary issues: 1) Women's Cooperatives heavily rely on savings and loan business units, leading to elevated levels of bad credit in the women's cooperatives of Blitar Regency; 2) Administrators of women's cooperatives struggle to diversify their businesses beyond savings and loans. The initiative commences with preliminary activities, involving a literature review followed by field research utilizing secondary data. Subsequently, a focus group discussion (FGD) is conducted to assess the actual conditions of women's cooperatives in the field, engaging with the Cooperatives and Small and Medium Enterprises (UMKM) Department. Through mentoring endeavors, the aim is to reinforce cooperative management, enabling the development of diversified business ventures beyond savings and loans. This is to be achieved through improved financial planning and activities. Additionally, the initiative aspires to instill in management a comprehensive understanding of business risk management.